RADIO--Robots in Assisted Living Unobtrusive, Efficient, Reliable and Modular Solutions for Independent Ageing - Karkaletsis, Vangelis; Konstantopoulos, Stasinos; Voros, Nikolaos S.; Annicchiarico, Roberta; Dagioglou, Maria; Antonopoulos, Christos P. (Springer International Publishing : Imprint: Springer, 2019)
This book describes a unique approach to bring robotic technology into elders' daily lives. Low cost components and low cost robotic assistants are effectively combined to offer high quality services to elders and people in need. The book presents in a comprehensive way how technology can be used for developing a new healthcare paradigm where high quality services are offered at home, thus reducing the ever-increasing hospitalization cost of the elders and the people with chronic diseases. Presents to an interdisciplinary audience IoT and robotic platforms combined in an efficient way for offering high quality services to elder end users; Discusses realistic paradigms - real houses (not labs) that have been developed using the technology described; Includes discussion of necessary IoT and CPS (cyber-physical systems) hardware architectures; Demonstrates Energy- and resource-efficient connectivity solutions.